2016
DOI: 10.1021/acs.energyfuels.6b01772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combustion and Emission Characteristics of an Indonesian Lignite Washery Tailing Slurry with a Bituminous Coal in a Bench-Scale Bubbling/Circulating Fluidized Bed Combustor

Abstract: In this study, the combustion and emission characteristics of slurry from an Indonesian lignite washery tailing (LWT) and a bituminous coal were studied and compared in both a bubbling fluidized bed (BFB) and a circulating fluidized bed (CFB). The effects of excess air ratio, feeding rate, secondary air ratio, and secondary air location on the flue gas emissions were analyzed to investigate the optimal operating conditions. The results show that it is feasible to directly fire LWT slurry in a CFB. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 31 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…Due to these low temperatures and short residence times, fewer CO molecules were converted to CO 2 , and more CO was emitted under higher PA flow rates in test C3. Similar phenomena have also been reported by Chen et al, Madhiyanon et al, and Varol et al…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Due to these low temperatures and short residence times, fewer CO molecules were converted to CO 2 , and more CO was emitted under higher PA flow rates in test C3. Similar phenomena have also been reported by Chen et al, Madhiyanon et al, and Varol et al…”
Section: Resultssupporting
confidence: 90%
“…This effect was due to the poor fluidization at low fluidizing air velocity, resulting in poor mixing conditions. Defluidization has been reported to occur when the PA flow rate decreases to 67 L/h in the present FB combustor . The decreased CO emission levels when the PA reached 78 L/h suggested that better fluidization and mixing conditions were achieved and that combustion was optimized.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The operation was optimal when the sludge content was between 20% and 30% wt. Recently, the comparison between combustion characteristics of CWM and lignite washery tails (a waste stream from lignite preparation) was obtained in a bench-scale CFB combustor (36 kWth) [66]. The authors reported similar combustion characteristics in terms of efficiency and emissions, complying with European and Chinese standards.…”
Section: Waste Derived Mixtures With Coal Addition (C-wasmix)mentioning
confidence: 86%
“…This is due to its significant amount of carbon content, which typically ranges from 40.30 to 48.43% [1,[3][4][5][6][7][8][9]. In the energy production, the amount of energy (known as higher heating value, HHV) that can be produced during the combustion of a fuel is vital [10], along with other requirements such as conversion efficiency, pollutant emissions, etc [11]. For the case of raw OPF, its HHV is typically considered low in the range from 16.3 to 18.1 MJ/kg [4][5][6][7][8][9][12][13][14].…”
Section: Introductionmentioning
confidence: 99%